Greek public archaeological museums in the 21st century: who manages them? - Καρναβά, Άρτεμις (Ariadne, 2021)
A TOPIC that recently caused a public debate in Greece is an administrative reform envisaged by the incumbent government; the reform regards the transformation of a number of public, state-run archaeological museums to legal entities that would be managed by a government-appointed board of trustees. The discussion that ensued presents us with an opportunity to ponder, once more, on the present and future of museums, of the archaeological finds kept in them and of their management by the state through its representatives, the archaeologists of the Greek Archaeological Service. In the current paper the matter is seen primarily as a property issue, an aspect which is current in international literature; yet, it also plays into a wider issue in the field of studies of past societies, namely to whom does antiquity ‘belong’ to, who has a right to speak about antiquity, and who has the right and the responsibility to manage the material remains of past societies.